Understanding and Responding to the Climate and Ecological Emergency: the Role of the Psychotherapist. (7th September 2022) - Tait, Adrian; O'Gorman, Jenny; Nestor, Rebecca; Anderson, Judith
Abstract : The authors outline the circumstances around the formation of the Climate Psychology Alliance and its purpose, before describing the CPA's current programme of psychologically informed support for those experiencing climate distress. The authors then describe research conducted by Adrian Tait examining feedback from participants of one of these methods of support, and summarize Rebecca Nestor's research around how organizational behaviour is influenced by social defences against unmanageable feelings. They conclude with a personal reflection by Jenny O'Gorman informed by psychodynamic theory on the experience of being a disabled counsellor engaged with climate activism. The authors highlight some of the ways in which CPA members' work has been taken up politically, and offer hope and agency for psychotherapists engaging with the climate and ecological emergency.